Twin Birth Study: 2-Year Neurodevelopmental Follow-up of the Randomized Trial of Planned Cesarean or Planned Vaginal Delivery for Twin Pregnancy. Issue 1 (March 2017) - Asztalos, Elizabeth V.; Hannah, Mary E.; Hutton, Eileen K.; Willan, Andrew R.; Allen, Alexander C.; Armson, B. Anthony; Gafni, Amiram; Joseph, K.S.; Ohlsson, Arne; Ross, Susan; Sanchez, J. Johanna; Mangoff, Kathryn; et al.
Abstract : ( Am J Obstet Gynecol. 2016;214:371.e1–371.e19) Twin pregnancies occur more often and present with complications in 2% to 3% of all deliveries. Earlier studies reporting reduced risk of adverse perinatal outcomes for one or both twins when delivered by elective cesarean delivery has led to increased rates of elective cesarean delivery. The Twin Birth Study, a randomized controlled trial, enrolled women with twin pregnancies to planned cesarean or planned vaginal deliveries. Primary analysis revealed that cesarean delivery did not alter the risk of fetal or neonatal death as compared to vaginal delivery. The secondary outcome was a combination of death or neurodevelopmental delay of the children at 2 years of age. This study presented the 2-year outcomes of the children in the Twin Birth Study.